South African Accounting Education Stocktake - Fouchè, Jaco; van der Merwe, Nico (African Sun Media, 2020)
This book is intended to take stock of the current state of accounting education with a specific emphasis on the South African situation. It provides a critical overview of the current published research and identified gaps. Through this, it aims to equip accounting academics with information and tools to motivate them to research the field of accounting education to improve teaching and learning. It also aids in the identification of suitable research topics in this regard and highlights potential pitfalls in researching accounting education. The book, therefore, focuses on accounting educators as specialists in their respective disciplines. Different authors with a keen interest in a specific area relating to accounting education research wrote each chapter in this book. It forms a planned collective work, assembled by appropriately qualified and experienced scholars in the accounting education field which generates a new conceptual synthesis that advances scholarship of accounting education research, since no such synthesis currently exists for accounting education research in South Africa.